Targeted Therapy on Age-Related Macular Degeneration - Vankodoth Sireesha; Kaluvala Ramya; Manne Nikshitha; Sunkari Nikitha; T. Rama Rao (TNOA Journal of Ophthalmic Science and Research)
Age-related macular degeneration (AMD) is an eye-related condition in developed countries and can affect elderly individuals to lose their central vision. At first, physicians can spot early AMD by looking for accumulation called macular deposits underneath the retinal pigment epithelium (RPE) cells. It can be broadly divided into dry and wet types. One can analyse dry AMD by seeing many large drusen, and RPE layer detachment leads to central vision impairment. However, wet AMD can be identified by formation of choroidal neovascularisation by using various diagnosis methods. There are many risk factors like genetics and environmental factors (smoking, diet) that can increase the chances of getting and worsening AMD. The main goal in treating AMD is to slow down the disease at an early stage. Anti-vascular endothelial growth factor medications are used to treat central vision loss patients in order to prevent new blood vessel growth, which helps lessen the loss of vision. A healthy diet rich in antioxidants may help in preventing AMD; understanding the risk factors and improving lifestyle choices are more important. Even though we have made good strides in spotting this disease for better treatment, we still need more research to really understand how it works to reduce disease conditions by various agents. This review article of AMD covers the recent trends in diseases, development of risk factors, diagnosis methods, grading system, and possibilities for AMD therapy.